Constitutionality of Recall Regulations for Officials Elected by the House of Representatives - Riqiey, Baharuddin; Khatami, Muhammad (Universitas Airlangga, 2025)
Efforts to disrupt the independence of state officials elected by the DPR did not stop at the time of the removal of the Constitutional Judge some time ago, rather the practice was again carried out undemocratically and then legitimized by law, commonly known as autocratic legalism, through the issuance of a revision of the DPR Regulation on Rules of Procedure. Therefore, the purpose of this study is to examine and analyze supervision from the perspective of administrative law and the constitutionality of DPR RI Regulation No. 1 of 2025. This research is a legal research using a statutory, conceptual, and case approach. This research is important to be carried out so that the implementation of judicial power, especially the Constitutional Court, remains an independent power and can uphold law and justice without intervention from any party. The results of this study indicate that the regulation of recall of state officials elected by the DPR from the perspective of administrative law supervision cannot be justified. In addition, DPR RI Regulation No. 1 of 2025 has the potential to violate the provisions of higher laws and regulations, the theory of the hierarchy of laws and regulations, the theory of independence, the theory of authority, the theory of separation of power, and the Constitutional Court Decision Number 103/PUU-XX/2022.